I Was Vey Amazed At The Solution 4

Calculus Level 5

Consider a function f ( x ) \displaystyle f(x) which satisfies f ( x ) = tan 2 x + π 4 π 4 f ( x ) d x \displaystyle f'(x) = \tan^2 x + \int _{-\frac{\pi}{4}}^{\frac{\pi}{4}} f(x) \ dx . If f ( π 4 ) = π 4 f\left(\dfrac{\pi}{4}\right) = -\dfrac{\pi}{4} , evaluate: 1000 π 4 π 4 f ( x ) d x \displaystyle \left \lceil -1000 \int _{-\frac{\pi}{4}}^{\frac{\pi}{4}} f(x) \ dx \right \rceil .

Notation: \lceil \cdot \rceil denotes the ceiling function .

Bonus: Identify the function f ( x ) f(x) .


For more problems like this, try answering this set .


The answer is 704.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Christian Daang
Apr 5, 2017

When integrated with respect to x, f ( x ) = ( tan x x ) + ( π 4 π 4 f ( x ) d x ) x + C \displaystyle\implies f(x) = ( \tan x - x) + \left(\int \limits_{-\frac{\pi}{4}}^{\frac{\pi}{4}} f(x) \ dx \right)x + C

Now,

f ( π 4 ) = ( tan ( π 4 ) π 4 ) + [ π 4 π 4 f ( x ) d x ] π 4 + C = π 4 C = 1 [ π 4 π 4 f ( x ) d x ] π 4 \displaystyle \begin{aligned} f\left(\dfrac{\pi}{4}\right) & = \left(\tan \left(\dfrac{\pi}{4}\right) - \dfrac{\pi}{4}\right) + \left[ \int \limits_{-\frac{\pi}{4}}^{\frac{\pi}{4}} f(x) \ dx \right]\cdot \dfrac{\pi}{4} + C = -\dfrac{\pi}{4} \\ \implies C & = -1 - \left[ \int \limits_{-\frac{\pi}{4}}^{\frac{\pi}{4}} f(x) \ dx \right]\cdot \frac{\pi}{4} \end{aligned}

Hence, f ( x ) = ( tan x x ) + [ π 4 π 4 f ( x ) d x ] x ( 1 + ( π 4 π 4 π 4 f ( x ) d x ) ) \displaystyle f(x) = ( \tan x - x) + \left[\int \limits_{-\frac{\pi}{4}}^{\frac{\pi}{4}} f(x) \ dx\right]x - \left(1 + \left( \dfrac{\pi}{4} \cdot \int \limits_{\frac{-\pi}{4}}^{\frac{\pi}{4}} f(x) \ dx \right) \right)

integrating both sides with respect to x x and whose limits is π 4 \cfrac{-\pi}{4} to π 4 \cfrac{\pi}{4} and let A = π 4 π 4 f ( x ) d x \displaystyle A = \int \limits_{\frac{-\pi}{4}}^{\frac{\pi}{4}} f(x) \ dx

A = ( ln cos x x 2 2 ) π 4 π 4 + ( A x 2 2 ) π 4 π 4 ( 1 + A π 4 ) x π 4 π 4 \displaystyle \implies A = \left. \left( -\ln |\cos x| - \dfrac{x^2}{2} \right) \right|_{\frac{-\pi}{4}}^{\frac{\pi}{4}} + \left. \left(\dfrac{Ax^2}{2}\right) \right|_{\frac{-\pi}{4}}^{\frac{\pi}{4}} - \left. \left( 1 + A\dfrac{\pi}{4} \right)x \right|_{\frac{-\pi}{4}}^{\frac{\pi}{4}}

As both ln cos x x 2 2 \displaystyle -\ln |\cos x| - \dfrac{x^2}{2} and A x 2 2 \displaystyle \dfrac{Ax^2}{2} are even functions, hence, when they are evaluated at limits a -a and a a , their result will be 0.

A = ( 1 + A π 4 ) x π 4 π 4 \displaystyle \implies A = - \left. \left( 1 + A\dfrac{\pi}{4} \right)x \right|_{\frac{-\pi}{4}}^{\frac{\pi}{4}}

\vdots

A = ( 1 + A π 4 ) ( π 4 π 4 ) A = ( 1 + A π 4 ) ( π 2 ) \displaystyle A = - \left( 1 + A\dfrac{\pi}{4} \right) \left(\dfrac{\pi}{4} - \dfrac{-\pi}{4} \right) \\ A = - \left( 1 + A\dfrac{\pi}{4} \right) \left( \dfrac{\pi}{2} \right)

\vdots A = π 2 A π 2 8 A ( 1 + π 2 8 ) = π 2 A = π 2 ( 1 + π 2 8 ) = 4 π 8 + π 2 \displaystyle A = - \dfrac{\pi}{2} - A\dfrac{\pi^2}{8} \\ A\left(1 + \dfrac{\pi^2}{8} \right) = - \dfrac{\pi}{2} \\ A = - \dfrac{ \dfrac{\pi}{2}}{\left(1 + \dfrac{\pi^2}{8} \right)} = - \dfrac{4\pi}{8+\pi^2}

\vdots

1000 π 4 π 4 f ( x ) d x = 1000 A = 1000 ( 4 π 8 + π 2 ) = 704 \begin{aligned} \displaystyle \implies \left \lceil -1000 \int \limits_{\dfrac{-\pi}{4}}^{\dfrac{\pi}{4}} f(x) \ dx \right \rceil = \left \lceil -1000A \right \rceil \\ = \left \lceil -1000 \left(-\dfrac{4\pi}{8+\pi^2}\right) \right \rceil = \boxed{704} \end{aligned}


Answer to the Bonus Question:

Since f ( x ) = ( tan x x ) + [ π 4 π 4 f ( x ) d x ] x ( 1 + ( π 4 π 4 π 4 f ( x ) d x ) ) \displaystyle f(x) = ( \tan x - x) + \left[\int \limits_{-\frac{\pi}{4}}^{\frac{\pi}{4}} f(x) \ dx\right]x - \left(1 + \left( \dfrac{\pi}{4} \cdot \int \limits_{\frac{-\pi}{4}}^{\frac{\pi}{4}} f(x) \ dx \right) \right) and

A = π 4 π 4 f ( x ) d x = 4 π 8 + π 2 \displaystyle A = \int \limits_{\frac{-\pi}{4}}^{\frac{\pi}{4}} f(x) \ dx = - \dfrac{4\pi}{8+\pi^2}

f ( x ) = ( tan x x ) ( 4 π 8 + π 2 ) x ( 1 ( π 4 4 π 8 + π 2 ) ) \displaystyle \implies f(x) = ( \tan x - x) - \left( \dfrac{4\pi}{8+\pi^2} \right)x - \left( 1 - \left( \dfrac{\pi}{4} \cdot \dfrac{4\pi}{8+\pi^2} \right) \right)

or simply, f ( x ) = ( tan x x ) ( 4 π 8 + π 2 ) x ( 1 π 2 8 + π 2 ) \displaystyle \boxed{f(x) = ( \tan x - x) - \left( \dfrac{4\pi}{8+\pi^2} \right)x - \left( 1 - \dfrac{\pi^2}{8+\pi^2} \right)}

Nice problem!

First Last - 4 years, 1 month ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...